P173 Etiological Factors For Adult Bronchiectasis Identified By A Specialized Investigation Protocol. (19th November 2012) - Creamer, A; Elliot, J; Ryan, J; French, J; Barker, H; Wat, DS; Baxendale, H; Exley, A; Haworth, CS; Floto, RA
Abstract : Rationale: Numerous factors have been identified as contributing to the development of bronchiectasis although their relative prevalence remains poorly understood. The Cambridge Centre for Lung Infection (CCRI) at Papworth Hospital has one of the largest specialist bronchiectasis units in Europe. All new patients referred with recurrent or severe chest infections undergo a systematic investigation protocol to determine an underlying cause for their lung disease involving: high-resolution CT (HRCT) scan; full pulmonary function tests; sweat testing and CFTR sequencing; nasal nitric oxide measurements; immunological test including serum immunoglobulins, specific antibody levels pre-and post vaccination, auto-antibody screening; Aspergillus serology and multiple sputum sample testing for conventional and mycobacterial microscopy and culture. We undertook an analysis of the results of these investigations to determine the relative contributions of causal factors in patients with bronchiectasis. Methods: We examined the results and case notes of all 352 patients referred to the CCRI with recurrent chest infections between January 1st 2009 and May 31st 2011. Of these, 202 individuals had HRCT evidence of bronchiectasis. The results of their initial investigations were analysed to determine the proportion of patients we could ascribe a likely cause for their bronchiectasis and whether this affected their subsequent management. Results: Using our investigation strategy, we were able to identify a likely cause in 139/202 (69%) patients, with 31% remaining idiopathic. Identifying an underlying cause frequently influenced subsequent patient management. Common causes included post-infection (22%), aspiration (7%), primary and secondary immune-deficiencies (4 and 6% respectively), and allergic broncho-pulmonary aspergillosis (6%). 5 new diagnoses of cystic fibrosis were made in patients aged 23, 26, 35, 53 and 64. Conclusion: This study represents the largest analysis of causative factors of bronchiectasis to date. Using our current investigation algorithm, we can ascribe a cause for bronchiectasis in almost 70% of new patients. Many of the underlying conditions diagnosed require specialist management.